2011
DOI: 10.1111/j.1365-2117.2011.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mechanisms driving detachment folding as deduced from 3D reconstruction and geomechanical restoration: the Pico del Águila anticline (External Sierras, Southern Pyrenees)

Abstract: The Santo Domingo Anticline (External Sierras, Southern Pyrenees), which separates the Jaca piggyback basin from the Ebro foreland basin, is a key structure of the Pyrenees. Its geometry has been interpreted both as a detachment fold and as a hangingwall anticline associated with an underlying thrust. In this paper, we present the results from a gravity survey and 2.5D gravity modelling carried out around the Santo Domingo Anticline. Density measurements indicate a sharp density contrast between the Triassic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…However, recent studies have demonstrated that the characteristics and the wavelength of folding in fold-and-thrust belts are strongly influenced by rheological parameters and 2014 mechanical isotropies of the stratigraphic pile (Yamato et al, 2011;Ruh et al, 2012). Therefore, future research will focus on mechanical reconstructions of fold-and-thrust belts (Simpson, 2009;Frehner et al, 2012;Vidal-Royo et al, 2012) including three-dimensional mechanical interaction of fold and fault growth (Schmid et al, 2008a;Grasemann and Schmalholz, 2012). (iii) A crystalline core zone forms the central and highest part of a mountain belt, usually above the orogenic root, where the crust is the thickest.…”
Section: Anatomy Of Orogens: the Critical Partsmentioning
confidence: 94%
“…However, recent studies have demonstrated that the characteristics and the wavelength of folding in fold-and-thrust belts are strongly influenced by rheological parameters and 2014 mechanical isotropies of the stratigraphic pile (Yamato et al, 2011;Ruh et al, 2012). Therefore, future research will focus on mechanical reconstructions of fold-and-thrust belts (Simpson, 2009;Frehner et al, 2012;Vidal-Royo et al, 2012) including three-dimensional mechanical interaction of fold and fault growth (Schmid et al, 2008a;Grasemann and Schmalholz, 2012). (iii) A crystalline core zone forms the central and highest part of a mountain belt, usually above the orogenic root, where the crust is the thickest.…”
Section: Anatomy Of Orogens: the Critical Partsmentioning
confidence: 94%
“…In the last decade, restoration methods integrating the mechanical properties of rocks have been proposed (De Santi et al 2002;Maerten and Maerten 2006;Moretti et al 2006;Moretti 2008;Guzofski et al 2009;Durand-Riard et al 2013). Although it is proved that accounting for rock mechanic parameters in the restoration offers greater precision and provides better accuracy for describing strain and stress fields (Durand-Riard et al 2010;Vidal-Royo et al 2012;Durand-Riard et al 2013), 3D conformable mesh generation is a significant challenge at large scale. Mesh generation is often time-consuming and requires a very large number of elements to honor fine-scale structural features, especially in complex faulted contexts (Moretti 2008;Caumon 2010;Durand-Riard et al 2010;Botella et al 2013).…”
Section: Restoration Goalsmentioning
confidence: 99%
“…In the context of geomodelling, the most common deformation methods are the Finite Element Method (FEM), mainly for restoration purposes (Durand-Riard et al, 2010;Maerten and Maerten, 2006;Moretti et al, 2006;Muron, 2005;Schmid et al, 2008;Siavelis, 2011;Vidal-Royo et al, 2012), the Discrete Element Method (DEM), mainly for studying rock deformation and tectonics (Burbidge and Braun, 2002; Scholtès and Donzé, 2013;Vidal-Royo et al, 2011), and Arbitrary Lagrangian-Eulerian Methods (ALE). They generally aim at producing an accurate simulation of physical rock behaviour.…”
Section: Overview Of Physically Based Deformation Algorithmsmentioning
confidence: 99%